Exploring the Impact of Yoga as a Mind-body Intervention for Cancer survivors – A Comprehensive Narrative Review - Krishna, B S Anantha; Sheelam, Praveen Kumar (International Research Journal of Ayurveda & Yoga, 2023)
This review explores yoga as a transformative mind-body therapy for cancer survivors, addressing the unique challenges they face post-treatment. Beyond conquering cancer, survivors contend with lingering fatigue, emotional turbulence, and diverse physical and psychological complexities during their survivorship phase. In response to these challenges, deeply rooted in ancient traditions, yoga emerges as a holistic approach to well-being. Tracing yoga’s evolution from ancient traditions to modern therapeutic practices, the narrative underscores its role as a source of ancient wisdom in contemporary healing. The philosophical foundations, drawn from texts like the Yoga Sutras of Patanjali, emphasize yoga’s holistic approach and its foundational concepts like “Ahimsa,” “Satya,” and “Santosha.” The review systematically delves into the benefits of yoga for cancer survivors: Enhancing physical well-being, fostering psychological and emotional resilience, and contributing to an improved overall quality of life. Supported by scientific evidence, yoga is shown to improve flexibility, strength, and balance, alleviate treatment-related side effects, and reduce stress, ultimately enhancing survivors’ vitality and quality of life. Key studies are synthesized, and strategies for implementing yoga in survivorship programs are outlined. Addressing potential barriers, the discussion emphasizes the adaptability of yoga practices, showcasing their tailoring to survivors’ varying needs. Collaborative integration into comprehensive care plans and evidence-based strategies for overcoming challenges is highlighted. In conclusion, the review advocates for the integration of yoga into comprehensive cancer care plans, presenting evidence-based insights that position yoga as a transformative and holistic modality in the journey to enhanced well-being for cancer survivors. Introduction: Cancer survivors face diverse challenges post-treatment, necessitating a holistic approach. This review explores the impact of yoga as a mind-body intervention for cancer survivors. Methods: A systematic literature search, including PubMed and ScienceDirect, identified peer-reviewed articles and clinical trials. Inclusion criteria focused on relevance and quality. Results: Yoga enhances physical well-being, addressing treatment-related side effects. Psychologically, it reduces stress and provides coping mechanisms. Emotional challenges are navigated through mindfulness. Quality of life improves holistically. Implementation strategies, tailored modalities, and multidisciplinary collaboration underscore feasibility. Discussion: Key studies validate yoga’s efficacy, offering a foundation for tailored survivorship programs. Challenges are addressed strategically, enhancing inclusivity. Conclusion: The narrative review advocates integrating yoga into cancer care, bridging ancient wisdom with modern healing practices. Evidence-based insights pave the way for a tailored, holistic approach, empowering cancer survivors on their journey to enhanced well-being.